Growth of genetically modified Saccharomyces cerevisiae and implementation of yeast estrogen assay (YES) and yeast androgen assay (YAS) - Vasquez Christodoulou, Marlen (My University, 2026)
Prof. John Sumpter and Dr. Edwin Routledge ▪ Growth of genetically modified Saccharomyces cerevisiae and implementation of yeast estrogen assay (YES) and yeast androgen assay (YAS) (2 weeks)